2019
DOI: 10.3390/app9224820
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Reliability Analysis of Rib-To-Deck Joints Using Test Data and In-Situ Measurements

Abstract: In this paper, the fatigue performance of rib-to-deck joints in orthotropic steel decks (OSDs) using thickened edge U-ribs (TEUs) and the OSD using conventional U-ribs (CUs) are investigated based on the fatigue test result and in-situ monitoring data. Firstly, comparative fatigue tests were carried out with full-scale rib-to-deck specimens. Probability–stress–life (P–S–N) curves were derived through the test data measured from a total of 18 specimens, including 7 CU specimens and 11 TEU specimens. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The result suggests that the influence of artificial flaws on the fatigue strength is almost negligible when their depth is below 1 mm. Zheng et al (2019a) performed a series of studies on the coupling mechanism of corrosion fatigue in weathering steels, as shown in Fig. 9.…”
Section: Development Of Weathering Steelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result suggests that the influence of artificial flaws on the fatigue strength is almost negligible when their depth is below 1 mm. Zheng et al (2019a) performed a series of studies on the coupling mechanism of corrosion fatigue in weathering steels, as shown in Fig. 9.…”
Section: Development Of Weathering Steelsmentioning
confidence: 99%
“…13. A series of studies (Heng et al 2020;Zheng et al 2019a;Heng et al 2017) have been carried out on the OSD with TEUs, as shown in Fig. 14. The result shows that the application of TEUs can improve the fatigue life of OSDs.…”
Section: Thickened Edge U-ribsmentioning
confidence: 99%
“…Li et al studied the influence of permeability on the fatigue properties of single-sided rib-todeck welded joints using the structural stress method, and the results showed that welded penetration had different effects on different fatigue failure modes [12]. Zheng et al improved the fatigue performance of single-sided rib-to-deck welded joints by changing the thickness of U-ribs [13]. Through finite element analysis, Ya et al found that in a largerib-deck model, increasing the thickness of the deck and improving the rigidity of the Scholars have tried to improve the fatigue performance of rib-to-deck welded joints through methods such as grinding, ultrasonic impact, and shot-peening, which improve the shapes of weld seams and reduce residual welding stresses.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of fatigue retrofits of diaphragm cutouts is often determined by the maximum concentration stress [23][24][25]. The cycling stresses and the magnitudes of stress amplitude lead to fatigue failure [26][27][28][29], which is also reflected in the "safe life" design [30][31][32]. It has been incorporated in the AASHTO LRFD code (AASHTO 2017), Eurocode 3 ("Design of steel structures"), and other specifications, where the S-N curve and similar algorithm of diaphragm cutouts are given based on nominal stress or hot spot stress [33,34].…”
Section: Introductionmentioning
confidence: 99%